MYSTIFICATIONS AND GAMES – ABOUT IDENTITY DISCOURSE IN MODERN BULGARIAN PROSE (ALEK POPOV) - Szydłowska, Joanna (Acta Neophilologica, 2010)
The object of the analysis are short prose works written by Bulgarian author Alek Popov. The manners of the defining of an identity of a modern person – taking into consideration a psychological, sociological and anthropological context – are conceptual. A concept of the identity has become a pretext for the description of chosen elements of the world introduced in Popov’s prose – such as space-time and creation of heroes.